All-In-One Optical Heater-Thermometer Nanoplatform Operative From 300 to 2000 K Based on Er3+ Emission and Blackbody Radiation - Debasu, Mengistie L.
A single nanoplatform integrating laser-induced heat generation by gold nanoparticles and temperature sensing up to 2000 K via (Gd,Yb,Er)2O3 nanorods is demonstrated, which presents considerable potential for nanoscale photonics and biomedicine. Blackbody emission is ascertained from the temperature increment with AuNP concentration, emission color coordinates as a function of the laser pump power, and Planck's law of blackbody radiation.